The impact of sleep quality on emotion regulation difficulties in adolescents: a chained mediation model involving daytime dysfunction, social exclusion, and self-control - Wenjuan Wang; Yuqiong Zhu; Hang Yu; Chengcong Wu; Tiancheng Li; Chenguang Ji; Yulian Jiang; Dongyan Ding (BMC, 2024)
Abstract Objective Previous studies have revealed associations between sleep quality and mental health, yet the comprehensive role of sleep quality, daytime dysfunction, social exclusion, and self-control in difficulties with emotion regulation remains unclear. This study aimed to elucidate how sleep quality affects emotion regulation difficulties among middle school students through pathways involving daytime dysfunction, social exclusion, and self-control, thereby providing a more comprehensive theoretical basis for mental health interventions. Methods Utilizing the pittsburgh sleep quality index, the adolescent social exclusion scale, the brief self-control scale, and emotion regulation scale-short form, we assessed 1067 students randomly selected from four middle schools from October to November 2023. After the removal of extreme values (those exceeding 3 standard deviations), 806 students were retained for data analysis. Results Our findings indicate that poor sleep quality significantly contributes to increased daytime dysfunction(β = 0.86, SE = 0.07, p < .001), which in turn affects social exclusion(β = 0.60, SE = 0.16, p < 0 0.001), self-control abilities(β = 1.27, SE = 0.16, p < .001) and emotion regulation difficulties(β = 1.56, SE = 0.30, p < .001). Social exclusion mediates the relationship between sleep quality and emotion regulation difficulties(Estimate = 0.11, SE = 0.04, 95% CI [0.04, 0.20] ). Conclusion The aim of this study is to provide new insights into the development of effective intervention measures to improve sleep and mental health in adolescents.